IL4 gene polymorphisms in Iranian patients with autoimmune hepatitis. (3rd May 2016) - Yousefi, Azizollah; Mahmoudi, Elham; Zare Bidoki, Alireza; Najmi Varzaneh, Farnaz; Baradaran Noveiry, Behnoud; Sadr, Maryam; Motamed, Farzaneh; Najafi, Mehri; Farahmand, Fatemeh; Rezaei, Nima
ABSTRACT: Background : Autoimmune hepatitis (AIH) is a chronic long-lasting hepatocellular inflammation associated with circulating auto antibodies. In addition to the genetic component, several cytokines have been implicated to be involved in AIH. This study was performed to investigate potential associations of AIH with IL4 gene variants. Method : The studied alleles and genotypes included: IL4G/T allele polymorphisms at position -1098 and C/T allele polymorphisms at two positions (-33 and -590) on the IL4 gene, in addition to the A/G allele polymorphisms at position +1902 on the IL4RA gene. Result : The IL4 C allele and CC genotype at position -590 and TT genotype at position -33 had a significantly higher frequency in AIH patients. Conclusion : This study identified the IL4 C allele and CC genotype susceptibility gene in AIH, which will provide better insights into the mechanisms of AIH and potential therapeutic interventions.